High support housing for people with serious mental illness in Canada: a scoping review - Alexandra Sosnowski; Mariana Ravazolli Martins; Eric A. Latimer; Eric A. Latimer; Frank Sirotich; Frank Sirotich; Julia Woodhall-Melnik; Nick Kerman; Vicky Stergiopoulos; Vicky Stergiopoulos (Frontiers in Psychiatry)
IntroductionMental health supportive housing aims to provide accommodation and support services to people with serious mental illness (SMI). Various supportive housing models have emerged in Canada post-deinstitutionalization, with heterogeneous and limited available information on congregate-based high support housing models (HSH) that provide 24/7 onsite supports. A registered scoping review was undertaken to identify the models and outcomes of HSH for people with SMI in Canada, including those exiting homelessness.MethodsFour academic databases (Medline, Embase, PsycINFO, CINAHL Plus) were searched, in addition to backward and forward citation searching and strategies for identifying grey literature. HSH configurations and outcomes (e.g., housing stability and preferences; physical and behavioral health; community integration, social support, and quality of life; costs) were investigated within the Canadian context.ResultsA total of 27,180 academic articles and 164 grey literature reports were initially screened. Following full-text review of 337 academic and 109 grey literature articles, and citation searching, a total of 58 academic articles and 31 grey literature reports were included in the review. The characteristics, objectives, and outcomes of HSH models were mixed. Three nonexclusive types of HSH were identified: [1] custodial HSH, [2] recovery-oriented HSH, and [3] alternatives to hospital programs and other institutions. Most studies were uncontrolled, though there was preliminary evidence to support improvements in HSH residents' health and functioning; gains in social support, quality of life, and community integration; reductions in housing and service costs, particularly when compared to the cost of inpatient hospitalization; and satisfaction with living arrangements, supports, and relationships. However, the findings were not unequivocal, and the diversity of methodologies and HSH models limited further comparisons of outcomes between the different types of HSH.ConclusionPeople with SMI experiencing complex and diverse needs can benefit from the services and supports provided by HSH. However, research on HSH is less developed compared to other, well-studied housing interventions. Further research on congregate housing settings, including their long-term outcomes and recovery-oriented practices, is warranted.